Is Cultural Fitness Hopelessly Confused?. (20th October 2015) - Ramsey, Grant; De Block, Andreas
ABSTRACT: Fitness is a central concept in evolutionary theory. Just as it is central to biological evolution, so, it seems, it should be central to cultural evolutionary theory (CET). But importing the biological fitness concept to CET is no straightforward task—there are many features unique to cultural evolution that make this difficult. This has led some theorists to argue that there are fundamental problems with cultural fitness that render it hopelessly confused. In this essay, we defend the coherency of cultural fitness against those who call it into doubt. 1 Introduction 2 Cultural Fitness is Not Superfluous 3 The Individuation Problem 3.1 The generations problem 3.2 Cultural growth versus cultural reproduction 4 The Repeated Learning Problem 4.1 The retention problem 4.2 Is fitness transitive? 5 Towards a Concept of Cultural Fitness 5.1 Biological and cultural individuals 5.2 Mutation and transmission biases 6 Conclusions